2014
DOI: 10.5032/jae.2014.04133
|View full text |Cite
|
Sign up to set email alerts
|

How Cognitive Style and Problem Complexity Affect Preservice Agricultural Education Teachers’ Abilities to Solve Problems in Agricultural Mechanics

Abstract: The purpose of this experimental study was to determine the effects of cognitive style and problem complexity on Oklahoma State University preservice agriculture teachers ' (N = 56)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This is consistent with the A-I theory that states that everyone has the ability to solve problems, regardless of cognitive style (Kirton, 2003). Similarly, Blackburn et al (2014) reported that most presevice agricultural education teachers were able to solve problems regardless of complexity or cognitive style. However, Pate and Miller (2011) found that the majority of secondary students were not able to troubleshoot a small gasoline engine compression problem successfully, regardless of whether they worked individually or employed the TAPPS method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the A-I theory that states that everyone has the ability to solve problems, regardless of cognitive style (Kirton, 2003). Similarly, Blackburn et al (2014) reported that most presevice agricultural education teachers were able to solve problems regardless of complexity or cognitive style. However, Pate and Miller (2011) found that the majority of secondary students were not able to troubleshoot a small gasoline engine compression problem successfully, regardless of whether they worked individually or employed the TAPPS method.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Blackburn et al (2014) recommended that students' ability to generate accurate hypotheses should be investigated to determine their effects on problem solving ability. Therefore, what effect does problem complexity, hypothesis generation, and cognitive style have on students' ability to solve authentic problems in agriculture?…”
Section: Conceptual Framementioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the TAPPS technique was inappropriate for use with secondary students because of their lack of domain specific knowledge (Pate & Miller, 2011b). Blackburn, Robinson, and Lamm (2014) conducted a study to investigate the problem solving ability of undergraduate students enrolled in a small gasoline engines course. The KAI was employed to determine the cognitive style of the students as being either more adaptive or more innovative.…”
Section: Problem Solving Research In Agricultural Educationmentioning
confidence: 99%